Morphological characterization of ticks of the genus Rhipicephalus (Boophilus) based on geometric morphometry: the case of the Savannah District in Côte d’Ivoire (Journal of Entomological and Acarological Research, 2023)
The introduction of the invasive tick Rhipicephalus (Boophilus) microplus in Côte d'Ivoire has led to a change in the population of ticks of the genus Rhipicephalus (Boophilus). Thus, this study aims to characterize morphologically the tick species of the genus Rhipicephalus (B.) by geometric morphometry. It consisted of collecting all ticks from cattle in 74 farms in the Savanes District. The collected ticks were identified in the laboratory and, after identification, only non-gorged adult ticks of the genus Rhipicephalus (B.) were retained for morphometric characterisation. A total of 394 ticks were examined under a digital microscope, images were digitised using the online program XYOM and the data were analysed. This study revealed that males of each species have a smaller average size than females. It also showed a variation in mean size in all species except for the females of Rhipicephalus (B.) decoloratus and Rhipicephalus (B.) geigyi whose mean sizes did not differ. Geometric morphometry allowed the separation of Rhipicephalus (B.) annulatus males from other males. In females, Rhipicephalus (B.) geigyi and Rhipicephalus (B.) microplus were distinguished from each other and from other females.
Keywords: Structuring; morphological; populations; ticks; Rhipicephalus; shape